Traditional Craft Conservation and Technological Innovation of Xuan Paper: An Exploration Applicable to Chinese Mixed-materials Art - Yinxue Wang (BioResources)
Xuan paper, an essential treasure of Chinese culture, has long been the heart of calligraphy and ink painting. This paper delves into the delicate balance between preserving the traditional craft of Xuan paper and embracing the innovation of modern technology, highlighting how these advancements have transformed its production process and expanded its role in contemporary mixed-media art. The traditional methods, rooted in skilled craftsmanship and natural materials, have served as the foundation for a material that can withstand centuries of artistic expression. With the rise of modern machinery and digital printing techniques, Xuan paper has evolved to meet the demands of today’s artists, offering enhanced durability and consistency while maintaining its unique texture. The fusion of old and new not only revitalizes this ancient art form but opens new avenues in contemporary art, where Xuan paper is now integrated with diverse materials and techniques. This editorial explores how technological innovations breathe new life into Xuan paper, providing artists with fresh tools for creative expression, while ensuring that its cultural heritage remains intact. Ultimately, this exploration aims to chart a course for the sustainable future of Xuan paper, making it relevant for both traditional and modern art forms.